2021
DOI: 10.1186/s13052-021-01063-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of correlated factors based on Pender health promotion model in brushing behavior in the 13–16 years old students of Guilan, Iran

Abstract: Background Tooth decay is one of the diseases that is closely related to people’s behaviors and it can have adverse effects on their performance and their success in the future. Brushing twice a day is the simplest and most effective way to reduce tooth decay. The study aim was to determining the roles of correlational factors based on the Pender’s health promotion model in brushing behavior of ninth grade students at urban public schools of Guilan province during the academic year 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
(39 reference statements)
5
16
3
Order By: Relevance
“…Among them, girls are easier to complete the promotion of health responsibility and nutritional behavior than men; In the three behaviors of stress management, social support and sports participation, men are easier to complete the promotion work; From the perspective of overall health promotion behavior, boys are more likely to complete health promotion than girls. These findings are similar to the results of many previous studies ( 31 33 ). This study also found that gender also affects adolescents' self-esteem, in which men have higher control perception than girls, while girls have higher evaluation orientation than men.…”
Section: Discussionsupporting
confidence: 93%
“…Among them, girls are easier to complete the promotion of health responsibility and nutritional behavior than men; In the three behaviors of stress management, social support and sports participation, men are easier to complete the promotion work; From the perspective of overall health promotion behavior, boys are more likely to complete health promotion than girls. These findings are similar to the results of many previous studies ( 31 33 ). This study also found that gender also affects adolescents' self-esteem, in which men have higher control perception than girls, while girls have higher evaluation orientation than men.…”
Section: Discussionsupporting
confidence: 93%
“…17 It has been widely applied to different health promotion behaviours, and has achieved substantial results. 18 19 The model includes three basic components that influence health-promoting behaviours as follows: (1) Open access cognitions and affection (perceived benefits of action, perceived barriers of action, perceived self-efficacy, situational influences, interpersonal influences and activityrelated affection); and (3) Desirable health-promoting behaviours. Individual characteristics and prior experiences assess previous relevant behaviours as well as the innate factors that influence health promotion behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Pender’s health promotion model (HPM) combines factors that may influence one’s behaviour, such as cognition, experience and society factors 17. It has been widely applied to different health promotion behaviours, and has achieved substantial results 18 19. The model includes three basic components that influence health-promoting behaviours as follows: (1) Individual characteristics and experiences (prior related behaviours and personal factors); (2) Behaviour-specific cognitions and affection (perceived benefits of action, perceived barriers of action, perceived self-efficacy, situational influences, interpersonal influences and activity-related affection); and (3) Desirable health-promoting behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…(Kajjura, Veldman and Kassier, 2019), and (Febriana and Nurhaeni, 2019). Articles discussing the application of the theory of Nola J. Pender health promotion model obtained 7 articles, namely his research (Shaahmadi et al ., 2019), (Bahabadi et al ., 2020), (Erenoglu, Rabiye, PhD; Can, Rana, PhD; Sekerci, Yasemin Gumus, 2019), (Goodarzi-Khoigani et al ., 2018), (Hepburn, 2018), (Haghi et al ., 2021), dan (Hosseini Khaboshan et al ., 2021)…”
Section: Resultsmentioning
confidence: 99%
“…Research (Hepburn, 2018) literation of health, self-efficacy, and readiness to change are variables related to health promotion behavior. Research (Haghi et al ., 2021) shows that perceived self-efficacy, situational influences, and perceived barriers to action have a significantly stronger relationship with commitment to plan of action. Research (Hosseini Khaboshan et al ., 2021) in the experimental group, the intervention program had a significant effect on all HPM constructs which included behavior outcome, and the estimates for prior behaviours, self-efficacy, interpersonal influences, feeling, perceived benefits and barriers, commitment, and behavior outcomes…”
Section: Resultsmentioning
confidence: 99%